Foregrounding Socio-political Dimensions of Learning Mathematics Some Field Observations from Delhi and Bihar - Gupta, Charu; Hussain, Md. Jawaid (JOURNAL OF INDIAN EDUCATION, 2023)
his paper goes beyond the socio-cultural perspectives and adopts a socio-political framework for analysing mathematics learning in and out of school settings. Besides describing the ‘funds of knowledge’ as embedded in children’s households, communities and work contexts, it also attempts to explore the interplay of power and identity with respect to mathematical practices in diverse contexts. To highlight these issues, we draw data from studies based on participation of children in everyday and work contexts in Delhi and rural Bihar. Through this paper, we attempt to foreground the notion of power while determining access to powerful ideas of mathematics as well as participation and achievement in mathematics.